Peran Pemuda dalam Kegiatan Adat Appalili di Kelurahan Baju Bodoa Kabupaten Maros - Risma Wati; Mrs. Nurlela (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to find out: (1) Knowing the series of implementation of the appalili custom in the Baju Bodoa Village, Maros Baru District, Maros Regency. (2) Find out how youth participate in preserving the appalili custom in the Baju Bodoa sub-district, Maros Baru District, Maros Regency. (3) Knowing the symbolic meaning and cultural values ​​contained in the appalili custom. This research uses a type of qualitative research which is analyzed and written descriptively. Data collection techniques used by using the method of observation, interviews and documentation. The results of this study indicate that (1) The implementation of the traditional appalili ceremony is carried out on November 16-17 every year with the following series, namely tidying up, maintaining/washing and plowing the fields using offerings and royal heirlooms. (2) The role of the youth in the traditional appalili ceremony is to spread invitations, entertain traditional councilors and other guests in a customary manner called (a'bembeng), hold heirlooms according to the tasks given by traditional stakeholders. (3) One of the meanings contained in the appalili traditional ceremony is as a form of request to Allah the Almighty so that the rice grows fertile with abundant harvests and contains cultural values ​​such as mutual cooperation, religion and gratitude..